On the Dynamics of Economic Growth - Sarel, Michael (IMF Working Papers; Working Paper ;, 1994)
This paper examines the dynamics of economic growth. First, it demonstrates that the standard neoclassical growth model with constant elasticity of intertemporal substitution is not consistent with the patterns of development we observe in the real world, once we consider the initial conditions. Second, it examines an alternative growth model, which is consistent with endogenously determined initial conditions and also generates dynamics that are in accord with the historical patterns of growth rates, capital flows, savings rates and labor supply. The alternative model is a generalized version of the neoclassical growth model, with increasing rates of intertemporal substitution due to a Stone-Geary type of utility.